The Internet of things foundation for smart cities, eHealth and ubiquitous computing - Armentano, Ricardo; Bhadoria, Robin Singh; Chatterjee, Parag; Deka, Ganesh Chandra (CRC Press, 2018)
This book provides a dual perspective on the Internet of Things and ubiquitous computing, along with their applications in healthcare and smart cities. It also covers other interdisciplinary aspects of the Internet of Things like big data, embedded Systems and wireless Sensor Networks. Detailed coverage of the underlying architecture, framework, and state-of the art methodologies form the core of the book.